PENGAWASAN PEMERINTAH TERHADAP EKSPLOITASI SUMBER DAYA AIR PERMUKAAN UNTUK KEPENTINGAN USAHA PENJUALAN AIR BERSIH DI DESA KEJI KABUPATEN SEMARANG - Ardhitya Eka Prasetya; Wiwik Widayati; Puji Astuti (Journal of Politic and Government Studies, 2015)
Abstract Semarang District is an area that has the potential of this highly abundant water. Potential Water Resources has strategic value to be developed as shown by the development of clean water sales efforts in Semarang Regency. Utilization large will bring greater implications. Starting from the reduced flow of water for irrigation needs and the needs of the surrounding community. Control of government becomes mandatory, as mandated by Article 33 paragraph 3 of the 1945